Chronic administration of the antidepressant fluoxetine impact on yersinia. Enterocolitica oral infection and reactive arthritis development in tnfr1 deficient mice - Funes, Samanta Celeste (2021)
Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRIs) with antidepressant and immunomodulatory effects. Whether FLX treatment impacts gastrointestinal bacterial infections and their sequelae, such as Reactive arthritis (ReA), remains unknown. We investigated the FLX effect on Yersinia enterocolitica (Ye) O:3 infection and ReA in a TNFR1 knockout mouse model. Differences in male and female mice were also evaluated. Male and female TNFR1 KO mice were orally infected with Ye O:3 (1-5x108 colony-forming units). From infection day, FLX (20 mg/kg/day) or water (control) was administrated in drinking water. On day 5, the number CFU was determined in stool, spleen, and mesenteric lymphoid nodes. The weight, mobility, mortality, and arthritis score of the mice were recorded. On day 21, splenic dendritic cells (DCs) infiltration and their maturation markers were evaluated by flow cytometry in surviving mice. We found that male TNFR1 KO mice have lower survival and higher clinical score after Ye infection. On day 5, FLX treatment increased bacterial dissemination in males. Surviving mice developed ReA but females treated with FLX showed greater severity than controls. Furthermore, FLX mice showed a lower proportion of splenic DCs without changing in CD86 expression. We conclude that TNFR1 KO male mice are more susceptible than females to Ye infection. The modulatory effect of FLX hinders more the immune response of males increasing systemic bacterial spread. Finally, the chronic administration of FLX did not reduce the severity of ReA and, in contrast, increased it in females. Although DCs infiltration in the spleen was reduced, the expression CD86 marker did not change, so we infer that the increased arthritis severity could be related to defective DCs migration. The results contribute to understanding how antidepressant chronic treatment influences the immune responses against pathogens and the maintenance of immune homeostasis.